PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 15 PANGKALAN NYIRIH - Fairunnizad, Fairunnizad; Kurniaman, Otang; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the fact that the students' science learning outcomes are low and there are still many students who have not reached the minimum completness criteria that has been set that is 65. From 26 students only 10 students (38.5%) reach minimum completnes criteria and 16 students (61.5% ) did not reach the minimum completness criteria. This research is a classroom action research conducted on the fourth grade students of SDN 15 Pangkalan Nyirih. The Research Instrument consists of Learning Tool used in this research based on Education Unit Level Curriculum (KTSP) or known as Curriculum 2006. Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The first meeting of the first cycle of teacher activity is the average activity of teachers observed in cycle II has increased compared to the cycle I. At the first meeting of the cycle I the average teacher activity 71.28% in either category, at the second meeting the average activity teachers increased to 78.58% in very good category.At the third meeting of cycle II the average of 82.14% of the teachers activity was very good and at the fourth meeting with the average activity of 85.71% in the Very Good category. The first meeting of the first cycle of student activity average of 62.5% with sufficient category, at the second meeting the average activity increased to 70.83% with good category.In the third meeting of cycle II the average student activity 83.33% in very good category and at the fourth meeting increased compared to the previous meeting with the average of 87.5% student activity with very good category. Student learning outcomes after preliminary student data above minimum completeness criteria only 10 people (66.42%) after cycle I increased up to 15 people (70.19%) after the second cycle increased more than 20 people (76.73%) the average of students acquired by class in the initial data is only 38.46 and after the first cycle increased by an average of 57.69 and in the second cycle increased more up to 76.92. This means that the classic value obtained by students has been above the minimum completeness criteria that has been set.Keywords: Think Pair Share Learning Model (TPS), Science Learning Outcomes